The Effects of Nebulized Inhaled Triptolide on Airway Inflammation in a Mouse Model of Asthma - Yafang Miao; Li Wei; Hao Chen; Zeming Zhang; Li Han (Canadian Respiratory Journal)
Inhalation of nebulized TP has received little attention in the past. Here, we intend to investigate the effect of nebulized inhaled TP on airway inflammation in a mouse model of asthma. 29 SPF BALB/c mice were divided into four groups: blank control (Blk, n = 5), normal saline (NS, n = 8), dexamethasone (Dex, n = 8), and TP (n = 8). During the process of sensitization, mice in the three intervention groups were treated with nebulized NS, an injection of Dex, and nebulized triptolide, respectively. Then bronchoalveolar lavage fluid (BALF), peripheral blood, and lung tissue were collected. Relevant cytokines, transcriptional factors, and CD4+Th17+ T cell proportions were assessed and compared. IL-6, IL-17, IL-23, and TGF-β1 demonstrated a significant difference between groups in the following order: Dex < TP < NS (P≤0.001), while IL-10 changed in the opposite direction (P<0.001). At the transcriptional level in lung tissue, the Ct value of IL-17 in the Dex group was significantly higher than in the NS and TP groups (P<0.001). Meanwhile, it was higher in the TP group than in the NS group (P<0.001). The Ct value of RORγt demonstrated a significant difference among three groups in the following order: Dex > TP > NS (P<0.001). An opposite trend of FoxP3 Ct value was revealed in the order: NS > TP > Dex. The proportion of CD4+Th17+ cells was 9.53 ± 2.74% in the NS group, 4.23 ± 2.26% in the Dex group, and 6.76 ± 2.99% in the TP group, which shows significant differences between the NS and Dex (P<0.001) or NS and TP groups (P<0.05). Inhalation of nebulized triptolide can play a role in suppressing airway inflammation with inflammatory cytokines and transcriptional factors reduced and CD4+Th17+ T cells dampened, also in a manner less than injected dexamethasone.